MENGEMBANGKAN KEPRIBADIAN UNTUK SUKSES SMA ERENOS - Paulus Yulius Fanggidae; Ririsma Sihombing; Antonius Juniarto; Yunianto Purnomo; Vionna Jaya (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Basically, in achieving success, you must have a character which must be able to have personality in carrying out every problem in all phases of life. Early age must be trained so that it has a dignity and also has a form of personality that has value for future provision. Success can be achieved and pursued by focusing on how each person tries to make progress in every process when doing something new within themselves. Success requires something which needs will in everyone and also every human being. Humans are equipped with curiosity so that they have other things in themselves with different values. Erenos High School needs it as a form and also part of the development of all students to achieve success in the future. The activities were carried out and also carried out with great enthusiasm which were carried out in the school hall. The activity received a good and also positive response and lots of feedback from the participants.